Liquid Viscosities, Surface Tension and Viscous Flow Thermodynamics of Ethylene Glycol + Water Mixtures at 308.15, 313.15, 318.15 and 323.15 K - Zhang, Likun; Li, Chunping; Huo, Tianrui; Guo, Zhenhua (Asian Journal of Chemistry, 2012)
This paper reports the measurements of viscosities and surface tension for the binary mixtures of ethylene glycol + water as a function of composition at T = (308.15, 313.15, 318.15 and 323.15) K. Viscosities were determined with an Ubbelohde capillary viscometer. The experimental results are compared with data published in the literatures. From the experimental data, viscosity, surface tension and viscosity deviations Dh were calcualted. The calculated results were fitted to a Redlich-Kister equation to obtain the coefficients and estimate the standard deviations between the experimental and calculated quantities. The values of Dh are negative over the whole concentration range. From the kinematic viscosity data, enthalpy of activation for viscous flow (DH*) and entropy of activation for the viscous flow (DS*) were calculated.